Platonisms : ancient, modern, and postmodern - Corrigan, Kevin; Turner, John Douglas. (Ancient Mediterranean and medieval texts and contexts. Studies in Platonism, Neoplatonism, and the Platonic tradition, 2007)
The present volume argues that Plato and Platonism should be understood not as a series of determinate doctrines or philosophical facts to be pinned down once and for all, but rather as an inexhaustible mine of possible trajectories. The book examines in this light different strands of Platonic thinking from the dialogues themselves through later Antiquity and the Medieval World into Modernity and Post-Modernity with new essays ranging from Descartes, Kant, Hegel, and Natorp to Yeats, Levinas and Derrida. And also suggests the possibility of reading the dialogues and the whole tradition resonating in and through them in new, unexpected ways.